EKSPLORASI TUMBUHAN BERACUN PADA TAMAN NASIONAL GUNUNG LEUSER RESORT SEI BETUNG , SUMATERA UTARA - Yosua Simanullang; Yunus Afifuddin; Aswita Hafni Lubis (Peronema Forestry Science Journal, 2015)
Indonesia is one nation that has a very extensive tropical forests. Types of diverse plant are largely not been identified promising a great opportunity as a source of useful chemical compounds. Biopesticides are one of the products made from poisonous plants that can be an alternative to the use of chemical pesticides. Biopesticide producing plant species very much and making it relatively easy. By utilizing a poisonous plant as biopesticides, the use of synthetic pesticides can be reduced. This study is expected to be the basis of research methods in the development of poisonous plants in Indonesia. This poisonous plant exploration research aims to identify and analyze the types of chemical compounds of poisonous plants in Gunung Leuser National Park Resort Sei Betung, North Sumatra. The method used is purposive sampling plots with spacious circular plot of 0.05 acres.This research had three phases. The first was aspect local knowledge with survey local knowledge. The second was aspect biodiversity with analysis of vegetation data collection. And the third was aspect phytochemical with detect the contain of secondary metabolit. The kinds of Poisonous plant found in the Gunung Leuser National Park Resort Sei Betung were Hibiscus heterophyllus, Crhysanemum sp., Macaranga denticulata, Macaranga hypoleuca, Pteruspermum javanicum, Artocarpus dadah, Macaranga gigantea, Clidemia hirta. The result of this research showed that all of kinds of aromatic plants contained secondary metabolit. Keywords: Eksploration, Poisonous plant, Phytochemical, Biopesticide.